A new species of planthopper from Costa Rica in the genus Oropuna from palms in lowland tropical rainforest - Bahder, Brian W.; Echavarria, Marco A. Zumbado; Barrantes, Edwin A. Barrantes; Helmick, Ericka E.; Bartlett, Charles R. (Zootaxa, 2021)
The derbid genus Oropuna is a small taxon of Neotropical planthoppers in the tribe Cenchreini comprised of three species. Recent survey work on palms for planthoppers in Costa Rica resulted in the discovery of a fourth species, Oropuna halo sp. n. In this study the new species is described and a key to the four species is provided along with sequence data for the cyctochrome c oxidase subunit I (COI) and 18S rRNA gene for the novel taxon.